Studies on productivity and characterization of polygalacturonase from Aspergillus giganteus submerged culture using citrus pectin and orange waste - Pedrolli, Danielle Biscaro [UNESP]; Gomes, Eleni [UNESP]; Monti, Rubens [UNESP]; Carmona, Eleonora Cano [UNESP] (Humana Press Inc, 2008)
Polygalacturonases are part of the group of enzymes involved in pectin degradation. The aim of this work was to investigate some of the factors affecting polygalacturonase production by an Aspergillus giganteus strain and to characterize this pectinolytic activity. Several carbon sources, both pure substances and natural substrates, were tested in standing cultures, and the best results were obtained with orange bagasse and purified citrus pectin. on citrus pectin as sole carbon source, the highest extracellular activity (9.5 U/ml and 40.6 U/mg protein) was obtained in 4.5-day-old cultures shaken at 120 rpm, pH 3.5 and 30 degrees C, while on orange bagasse, the highest extracellular activity (48.5 U/ml and 78.3 U/mg protein) was obtained in 3.5-day-old cultures shaken at 120 rpm, pH 6.0 and 30 degrees C. Optimal polygalacturonase activity was observed in assays conducted at pH 5.5-6.5 and 55-60 degrees C. The activity showed good thermal stability, with half-lives of 90 and 30 min when incubated at 55 and 60 degrees C, respectively. High stability was observed from pH 4.5 to 8.5; more than 90% of the activity remained after 24 h in this pH range.
Keywords: polygalacturonase; pectinolytic enzyme; orange waste; citrus pectin; enzyme characterization; Aspergillus giganteus